Climate Change in China and Its Effects on the Sustainable Efficiency of Agricultural Land Use - Mengfei Song; Shuo Qing; Qiuyi Wu; Honghui Zhu (Land)
Understanding the effects of climate change on agricultural land green use efficiency (AGUE) is vital for shaping adaptive technologies and agricultural policies. Utilizing data from 30 Chinese provinces (2003–2022), this study applies the Geographically and Temporally Weighted Regression (GTWR) model to assess how climate change impacts AGUE and its spatial–temporal variations. Studies show that China’s climate demonstrates significant interannual variability and spatial heterogeneity. The regression coefficient of the annual precipitation is positive and gradually decreases from the periphery to the center. AGUE across provinces is declining and exhibits significant spatial clustering characteristics. The spatial–temporal analysis indicates that the annual average temperature has a significant negative impact on AUGE, and the regression coefficient decreases from southeast to northwest. The regression coefficient of the annual precipitation is positive and gradually decreases from the periphery to the center. Extreme weather conditions have negative impacts of varying degrees on inter-provincial climate change. The findings provide a reference for the green transformation and development of agriculture in China.